1989
DOI: 10.1159/000213001
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise Increases Natural Cellular-Mediated Tumor Cytotoxicity in Elderly Women

Abstract: The influence of acute treadmill exercise on natural killer (NK) cell tumor cytotoxicity in vitro was studied in elderly women after participation in a program of physical exercise training (PET) (n = 7) or after participation in a paralleling nonexercise control (NEC) condition (n = 7). The two study groups were equated (p > 0.05) according to age, percent total body fat, functional status as measured by multi-inventory ranking, and exercise capacity. After the experimental period, the PET subjects had a grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
6

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 11 publications
3
64
0
6
Order By: Relevance
“…As for life style, it was reported that reduction of NK cell functions was associated with cigarette smoking [34][35][36][37][38] , shortened daily sleep 17) , disturbed sleep [39][40][41] , circadian rhythm (high activity in the morning and low activity at night) [42][43][44][45] , and excessive physical exercise 46,47) . Conversely, healthy life styles (i.e., good sleep, adequate physical exercise, and so on) were associated with increases of NK cell functions [48][49][50] . Several occupational health studies [15][16][17][18][20][21][22][23][24][25] of workers have reported that reduction of NK cell functions (including CD56) was associated with night shift work 15) , long work 16,17) , depression 18) , job stress 20,25) , and burnout 24) .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As for life style, it was reported that reduction of NK cell functions was associated with cigarette smoking [34][35][36][37][38] , shortened daily sleep 17) , disturbed sleep [39][40][41] , circadian rhythm (high activity in the morning and low activity at night) [42][43][44][45] , and excessive physical exercise 46,47) . Conversely, healthy life styles (i.e., good sleep, adequate physical exercise, and so on) were associated with increases of NK cell functions [48][49][50] . Several occupational health studies [15][16][17][18][20][21][22][23][24][25] of workers have reported that reduction of NK cell functions (including CD56) was associated with night shift work 15) , long work 16,17) , depression 18) , job stress 20,25) , and burnout 24) .…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that NK cells defend against tumor cell growth and viral infections in human cellular immune systems, and that NK cell functions are variously influenced by workload [15][16][17] , mental health 20-22, 24, 25) , and life style [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] . As for life style, it was reported that reduction of NK cell functions was associated with cigarette smoking [34][35][36][37][38] , shortened daily sleep 17) , disturbed sleep [39][40][41] , circadian rhythm (high activity in the morning and low activity at night) [42][43][44][45] , and excessive physical exercise 46,47) .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7], metabolic hormones [8,9], muscular hypertrophy [9,10], the immune system [11][12][13], and antioxidant enzymes [14,15]. Exercise also produces a positive effect on the psychological and emotional state and alleviates stress [16].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a healthy lifestyle (e.g., adequate sleep and regular physical exercise) has been associated with increased NK cell function 11,34,35) . In many such studies, researchers have utilized NKCA as a health index.…”
mentioning
confidence: 99%